Academic Library Features and Postgraduate Student Users’ Satisfaction in Selected Public Universities in Southern Nigeria - Arochi, Joseph Michael (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2025)
This study examines the extent to which academic library features affect user satisfaction for postgraduate students in Southern Nigeria using a cross-sectional framework. The study involves a sample of three (3) public universities in Southern Nigeria. 141 survey data collected using a Likert structure questionnaire were analyzed. The empirical analysis is based on OLS regression cross-sectional model that incorporates location and space, materials/collections, facilities, staff, and programs and services as exogenous variables while incorporating intention to reuse and intention to recommend as endogenous variables. The study measurement model was validated using confirmatory factor analysis CFA. The study found that intention to reuse is strongly and positively triggered by improved library programs and services as well as adequate and accessible location and space. Materials/collections and staff were found to insignificantly affect intention to reuse. While intention to recommend was found to be enhanced by improved attitude and ability of library staff. Finally, our findings show, amongst other things, that except for library staff, all other variables of location and space, materials/collections, programs and services have positive but insignificant effects on postgraduate students’ intention to recommend the library. The theoretical and practical implications of these findings are discussed. The study concludes that academic library features largely influence postgraduate student users’ satisfaction. Accordingly, recommendations were provided in line with the research findings and conclusion.